RELATIONSHIP BETWEEN MYOCARDITIS AND DENGUE - Melo Lopes, Rafael; Dantas Fernandes Veras, Yana; Zenette Alves Guedes Da Silva, Janielly; De Sena Bernardo, João; Paulo de Sena Rodrigues, Marcos; De Holanda Angelim Santos, Sean; Eloisa De Castro Lima, Maria; Dário Coelho Campelo, Raimundo; Gomes Ripardo de Azevedo, Orleâncio; Gondim Moreira, Raquel (Health and Society, 2024)
Introduction: Myocarditis, an inflammation of the heart muscle, can arise as a complication of dengue fever, a mosquito-borne disease. It is essential to adopt a multidisciplinary approach to monitor and treat cardiac complications in patients with dengue fever at an early stage. Diagnostic tests include serology, PCR, and echocardiography. From a review study on cardiac involvement in dengue, it was found that this complication is significant and demands a multidisciplinary approach . Objective: The objective of this study was to conduct a comprehensive integrative review to explore the relationship between myocarditis and dengue fever. Methodology: Articles were searched in databases such as PubMed, Google Scholar,Ministry of Health, and ScienceDirect, using search terms in both Portuguese and English. Out of 122 articles found, 74 were selected for analysis, and 13 were included in the results. Results: The studies examined the relationship between dengue fever and myocarditis, with a focus on the cardiovascular manifestations of dengue fever and the prevalence of myocarditis in infected patients. Analysis of the articles revealed a significant prevalence of myocarditis in patients with dengue, highlighting a strong association between the two conditions. Discussion: Dengue patients frequently present with cardiac issues such as myocarditis, necessitating early detection to prevent serious complications. Effective vector control is crucial to reducing the impact of dengue. These findings provide direction for future research and the development of targeted therapies. Conclusion: Early identification of cardiac complications, such as myocarditis in dengue patients, is crucial to reducing morbidity and mortality. Ongoing research into the pathophysiological mechanisms is vital for the development of specific treatments. The study concludes that myocarditis is commonly associated with dengue, requiring meticulous medical monitoring.